Інформаційна природа структуроутворюючих складових економічної системи - Конохова, Зоя Петрівна; Харченко, Алла Олександрівна (Національний авіаційний університет, 2018)
У статті розглядається роль інформації у процесі формування та функціонування економічної системи. Визначається інформаційна сутність зв'язків між елементами системи та відносин власності як її основної структуроутворюючої складової. Запропоновано визначення власності як сукупності даних про режим доступу економічних суб'єктів до обмежених ресурсів або благ. Здійснено інформаційний опис категорії "власність" шляхом висвітлення трьох її основних аспектів: структури категорії, економічної та правової реалізації власності. Підкреслюється важливість чіткої специфікації прав власності з метою зменшення невизначеності економічного середовища та формування у індивідів стабільних очікувань щодо результатів їхніх дій або відносин з іншими економічними агентами. Звертається увага на те, що спотворення інформації щодо розподілу та захисту прав власності призводить до підвищення невизначеності в економічній системі та може використовуватись суб'єктом управління з метою отримання неправомірної вигоди.

Researching of development and efficiency functioning of the economy in the conditions of the formation of an information society actualized the problem of studying the informational essence of the economic system and factors that determine it. In the process of functioning, the economic system and its components are generated signals about their presence, characteristics, interaction, dynamics. These signals are perceived by the observer as data on the parameters of the subject systems and turn into information. Information is becoming the data case if there is a certain value for the observer. The role of information in the functioning of the economy is being investigated mainly within the firm or market, in decision-making processes entrepreneurs or consumers. Information characteristics of the economy as systems are still underdeveloped. It must be recognized that any connection between the elements of the economic one systems are mediated by information flows. Informational nature has the influence of the subject of management on the elements of the economic system and the processes that occur in it. Interactivity of this interaction (reverse communication) provides for the adoption of management decisions, their implementation and correction. The development of economic systems is accompanied by an increase in the number rotational information, and the number of acts of exchange of information. It causes an increase in the intensity of the links between the elements of the system that leads to the formation of a more effective structure and increase it sustainability (stability). The structure-creating factor of any economic system is property relations. From the information point of view, these relationships can be present as data about the access regime to the limited resources (blessings) which perceived by interested parties for the purpose of use or exchange and turn into legal information. Specification of property rights, that is legal establishment information on the access regime to limited economic resources (good), and the proper protection of this mode ensures the formation of a stable one economic environment, reduces its uncertainty and contributes the formation of stable expectations of individuals about the results of their actions or relations with other economic agents.
Information nature of structural creativity composition of economic system
Keywords: інформація; економічна система; власність; інформаційна сутність власності; невизначеність; специфікація прав власності; information; economic system; property; information essence of property; uncertainty; specification of property rights